Validasi Modul Bermain Peran “Aku Sayang Kawan” untuk Meningkatkan Pengetahuan Perilaku Prososial pada Anak Usia Dini - Sita Alfiyah; Wisjnu Martani (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2015)
The aim of this research is to carry out the validation of role play module “Aku Sayang Kawan” to improve the knowledge of prosocial behavior in the early age children. The hypothesis of this research was that the role playing module “Aku Sayang Kawan” could improve the knowledge of prosocial behavior in the early age children. The method of this  research was the untreated control group design with dependent pretest and post test sample design experiment. The participants of this research were separated into control group (13 children) and experiment group (11 children). The result of statistical test using anova mixed design was the score F=27.20 (p<0.01). It means that there was significantly different knowledge score of prosocial behavior from pretest to post-test between experiment and control groups. The role play module “Aku Sayang Kawan” could be applied to improve the knowledge of prosocial behavior in the early age children.